The Influence of Service Solvency and Financial Independence on Financial Sustainability in Provincial Governments on the Island of Sumatra - Melfiana, Bunga; Frymaruwah, Edwin; Sulaiman, Sulaiman (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of service solvency and financial independence on financial sustainability. Financial sustainability is the ability of a local government to fulfill its obligations in providing services to the public, both now and in the future. Factors such as service solvency and independence are believed to influence financial sustainability in provincial governments on the island of Sumatra. This study used a quantitative approach with a saturated sampling technique involving 10 provincial governments on the island of Sumatra. Data were collected through the e-PPID website of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) in the form of Audit Reports of the Republic of Indonesia for 2019-2023. Data were analyzed using panel data multiple regression to examine the relationship between variables. The results indicate that service solvency and financial independence, both partially, have a positive and significant effect on financial sustainability. Simultaneously, service solvency and financial independence have a significant effect on financial sustainability. This study concludes that improving service solvency and financial independence can enhance and promote financial sustainability. Therefore, local governments need to continue improving these two factors to encourage good, equitable, and high-quality public services, thus supporting financial sustainability.